Pension Reform in Belgium. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper reviews the financial implications of aging for the pension system in Belgium during 1995-2050. Our simulations indicate a strong rise in pension expenditure over the next half century, as is the case in other industrialized countries. In Belgium, the problem is particularly acute in the pension system for civil servants. The impact of amending indexation of pension benefits and their ceilings, of harmonizing pension schemes for public and private sector employees, and of increasing the mandatory retirement age is discussed. We also calculate rates of return on the participation in the Belgian pension system and present some evidence on the intergenerational impact of the different reform options.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet